POSTHUMANISM IN TWO FANFICTION STORIES: THE CYBORG AND CYBORG - Maria Vincentia Eka Mulatsih (Sanata Dharma University, 2020)
Since the development of Artificial Intelligence (AI) has widely spread in many sectors of humans life, the studies of posthumanism where humans ask critically about their existence are needed. Knowing that, this research will deal with posthumanism (Herbrechter, 2015) drawn from two fanfiction stories entitled The Cyborg and Cyborg. Both stories are written by different authors from different countries. This study is a library research which applies comparative study as part of data analysis technique and the result of data analysis will be presented qualitatively. Preliminary result that is taken from first reading of the two stories deals with young authors who think that cyborgs have more humanistic values when they are being compared to humans. The researcher hopes that this study has insightful effect to pre-service students in dealing with the development of technology in this revolution industry 4.0.